Novel approaches to treating symptoms and slowing the progress of neurodegenerative diseases - Tobin, Andrew B. (Henry Stewart Talks, 2019)
Brief overview of dementia, Current treatments for Alzheimer’s disease, Role of muscarinic receptors in learning and memory, Using prion disease as a model, Effects of muscarinic receptor drugs on learning and memory deficits in prion disease, Types of drugs for different stages of Alzheimer’s disease